Effect of caffeine on attack decision-making in trained beach volleyball players following prolonged cognitive effort induced by social media use: a randomized, single-blind, crossover pilot study - Costa, Y. P.; Lopes-da-Silva, B. S.; Fonseca, F. S.; Albuquerque, M.; Batista, G. R.; Fortes, L. S. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Mental fatigue is a psychobiological state characterized by a feeling of tiredness or lack of energy after performing cognitive activities. Recently, studies have found that prolonged use of social media can cause mental fatigue and consequently impair decision-making performance in athletes. On the other hand, caffeine may counteract mental fatigue by antagonizing adenosine. Therefore, this study aimed to analyze the effect of caffeine on the attack decision-making skill of trained beach volleyball players after prolonged cognitive effort by using social media on smartphones.